Live Concert Performance: An Ecological Approach. Issue 1 (2nd January 2016) - Behr, Adam; Brennan, Matt; Cloonan, Martin; Frith, Simon; Webster, Emma
Abstract : For the last decade we have been engaged in the study of the history, economics, and sociology of live music in Britain. In this article we will consider the value of "ecology" as an analytic concept (rather than just a buzzword) and compare an ecological account of the setting in which music happens to the use of previous spatial metaphors, from Durkheim's milieus to Straw's scenes. To illustrate our argument, we present case studies of three Scottish concerts: one in a small-scale venue (Glasgow's King Tut's), one in a mid-size venue (Edinburgh's Queen's Hall), and one in a large-scale venue, the 12, 000-seater SSE Hydro.